The anti-competitive practices of the internet giants corporations in the brazilian context (2018)
The networked society promotes the use of information and communication technologies, especially the Internet. Large companies acting in this way establish themselves as real “giants” and determine new power dynamics and challenges to a democratic regulation of the Internet. The work seeks to map some anti - competitive practices of the “giants of the Internet” from the analysis of some decisions of the Administrative Council of Economic Defense in the Brazilian context and other bodies responsible for inhibiting trust practices in the international environment; for such, it uses a deductive approach, from a systemic - complex background plan. It also seeks to develop reflections on the possibility of a democratic regulation aimed at preventing abuses of these “Internet giants”.